Is Patient Selection Important for Hip Resurfacing? - Nunley, Ryan M. (Springer-Verlag, 2008)
The optimal implant option for hip arthroplasty in the young, active patient remains controversial. There has been renewed interest for metal-on-metal hip resurfacing due to improved design and manufacturing of implants, better materials, enhanced implant fixation, theoretical advantages over conventional total hip arthroplasty, and recent Food and Drug Administration approval of two devices. Recent studies indicate satisfactory short- and midterm clinical results (1- to 10-year followup) with low complication rates, but there is a learning curve associated with this procedure, a more extensive surgical approach is necessary, and long-term results have yet to be determined. Proper patient selection may help avoid complications and improve patient outcomes. Patient selection criteria in the literature appear based predominantly on theoretical considerations without any consensus on stratifying patient risk. The most commonly reported complications encountered with hip resurfacing include femoral neck fracture, acetabular component loosening, metal hypersensitivity, dislocation, and nerve injury. At the time of clinical evaluation, patient age; gender; diagnosis; bone density, quality, and morphology; activity level; leg lengths; renal function; and metal hypersensitivity are important factors when considering a patient for hip resurfacing. Based on our review, we believe the best candidates for hip resurfacing are men under age 65 with osteoarthritis and relatively normal bony morphology. Level of Evidence: Level V, prognostic study. See the Guidelines for Authors for a complete description of levels of evidence.